Does going easy on distressed banks help economic growth? - Sean Hundtofte (Federal Reserve Bank of New York, 2017)
During banking crises, regulators often relax their normal requirements and refrain from closing financially troubled banks. I estimate the real effects of such regulatory forbearance by comparing differences in state-level economic outcomes by the amount of forbearance extended during the U.S. savings and loan crisis. To instrument for forbearance, I use historical variation in deposit insurance - and hence supervision - of similar financial intermediaries (thrifts) and exploit fixed differences between regional supervisors of the same regulator. The evidence suggests a policyinduced increase in high-risk loans during the official forbearance period (1982-89), followed by a broader bust in house prices and real GDP.
Keywords: G01; G2; H12; 330; financial crises; regulatory policy